Comparing CMR Mapping Methods and Myocardial Patterns Towards Heart Failure Outcomes in Non-Ischemic Dilated Cardiomyopathy - Vita, Tomas (JACC Cardiovasc Imaging, 2018)
OBJECTIVES: In patients with non-ischemic dilated cardiomyopathy (NIDCM), native T1, partition coefficient (λ(Gd)), and extracellular volume fraction (ECV) mapping may offer prognostic values beyond late gadolinium enhancement (LGE), by scaling the range of myocardial changes. BACKGROUND: In patients with NIDCM, LGE is seen in 30% of patients and it indicates adverse prognosis. METHODS: We mapped 6 anatomical locations using all 4 CMR tissue characterizing methods and associated with outcome. We performed T1 mapping of the myocardium and the blood pool, before and serially after contrast injection, using a look-locker cine gradient-echo technique to obtain T1 and the corresponding reciprocal R1 values. λ(Gd) values were derived from the slopes of the least-squares regression lines for myocardial versus blood R1, then adjusted to serum hematocrit to yield ECV. RESULTS: Consecutive 240 NIDCM patients (49±16years; 38%female) underwent CMR for cardiac function, LGE, native T1, λ(Gd), and ECV. After a median of 3.8 years, 36 (15%) experienced adverse events (MACE) including 22 heart failure hospitalizations and 14 deaths. Non-ischemic LGE was detected in 34% whereas ECV was elevated (≥1 location) in 58%. Comparing the 4 methods, mean ECV and λ(Gd) both demonstrated strong association with MACE (both p<0.001). In contrast to native T1 and LGE, ECV values from all 6 locations were associated with MACE and death, with the anteroseptum being the most significant (p<0.0001). The number of abnormal ECV locations correlated linearly with annual MACE rates (p=0.0003). Mean ECV (%) was the only predictor to enter a prognostic model that contained age, gender, NYHA, and LVEF. For every 10% increase, mean ECV portended to a 2.8-fold adjusted increase risk to MACE (p<0.001). CONCLUSIONS: In this study of patients with NIDCM, mapping the myocardial extent of abnormality using ECV offers prognostication towards heart failure outcomes incremental to LGE or native T1 mapping.